The impact of using program visualization techniques on learning basic programming concepts at the K–12 level - Mladenović, Monika; Žanko, Žana; Aglić Čuvić, Marin (Computer applications in engineering education, 2021)
Novices enrolled in introductory programming courses often face many difficulties. These difficulties are more emphasized when novices are K–12 students. Many new visual programming languages have primarily been designed to provide a smooth introduction to programming for children. However, at some point, a general‐purpose text‐based programming language should be used. A well‐known and studied method is to visualize program execution to assist novices in forming correct mental models. Although many studies have investigated the effects of using visualizations in teaching and learning, most of them focus on courses taught at the university level. Studies that focus on investigating the impact of program visualizations at the K–12 level are, to the best of our knowledge, scarce. Therefore, we investigated the impact of using program visualizations with a group of K–12 students. Because of the underrepresentation of girls in computer science and known gender stereotypes, we additionally investigated student performance based on gender. Our research included 98 fifth‐grade students from three elementary schools. The lectures in the experimental group included different visualization techniques, including a program visualization tool and PowerPoint animations, whereas the control group had no program visualizations. All students learned Python as part of their curriculum. We present the results of our research in this paper.